TATA LAHAN DAERAH RUMPIN DENGAN MENGGUNAKAN METODE PEMBOBOTAN MORFOMETRI - Suherman Dwi Nuryana; Arini Dian; A. Kadyanto Kadyanto; Shahnaz B; Muhammad Adimas Amri (Universitas Negeri Padang, 2022)
Rumpin is an area close to the capital city and is an area that is developing geology. Rumpin area is mostly formed by Quaternary surface deposits (Alluvium, Pematang Pantai, Fan Alluvium and Tufa Banten) and a small part (southern) is Tertiary sedimentary rock (Genteng Formation and Serpong Formation). The Rumpin area does not yet have a land use, the regional potential and the potential for disasters in the area are very large, especially flood disasters because the area is crossed by the Cisadane river. Flood is a disaster that often occurs and can cause huge losses from various parties. Therefore, a study is needed to classify flood-prone areas as an effort to mitigate flooding. The Cisadane watershed area is an area that will be studied using a Geographic Information System (GIS). GIS can be used to classify sub-watersheds that are considered flood-prone areas. The data used is the Topographic Map 1: 100,000 from the SRTM data. The method used is the scoring method, namely morphometric, geomorphological and land use planning parameters, which are then weighted and scored according to their flood vulnerability by utilizing a geographic information system (GIS) so that they can classify flood-prone area objects in digital form in the area.